Role of long non-coding RNA NEAT1 in the prognosis of prostate cancer patients. Issue 22 (29th May 2020) - Bai, Junchao; Huang, Guangyi
Abstract : Abstract: Prostate cancer is the second leading cause of cancer-related deaths among male population worldwide, its incidence and lethality steadily increase. Nuclear enriched abundant transcript 1 (NEAT1) is a long non-coding RNA (ncRNA), located on chromatin 11. It has been found to function as an oncogene in different kinds of cancer. However, until now, the clinical significance of NEAT1 has not been investigated in prostate cancer. Paired tissue specimens of prostate cancer and matched normal prostate tissues were obtained from 130 patients with prostate cancer between 2014 and 2019 at The Fourth Affiliated Hospital Zhejiang University, School of Medicine. Group means were compared using the Student t test. Chi-Squared test was used for analyzing the correlation of the expression of NEAT1 with clinicopathologic features of prostate cancer patients. Survival data was analyzed using the Kaplan–Meier estimate and log-rank P was calculated. Cox regression model was used for univariate and multivariate analysis for factors related to overall survival. The expression of NEAT1 was increased significantly in prostate cancer tissues, compared with adjacent normal prostate tissues ( P < .001). NEAT1 expression was significantly associated with TNM stage ( P = .005), lymph nodes metastasis ( P = .005), distant metastasis( P = .003), and Gleason score ( P = .001). Overall survival rate was significantly lower for prostate cancer patients with a high expression level of NEAT1 than those with a low NEAT1a expression level ( P = .048). In multivariate analysis, the results showed that the expression of NEAT1 was an independent prognostic factor for overall patient survival (HR: 2.111, CI: 1.735–10.295, P = .039). In the present study, NEAT1 is identified as an important lncRNA that may predict the prognosis of patients with prostate cancer.